Factors Responsible for Post Graduate Resident Satisfaction Working in Medicine, Surgery and their Allied Departments in Bahawal Victoria Hospital, Bahawalpur, Nishtar Hospital Multan and Jinnah Hospital Lahore (Medical Forum Monthly, 2024)
Objectives: The objective of the study was to evaluate the factors responsible for Post Graduate Resident satisfaction working in medicine, surgery and allied departments in BVH, NHM, and JHL.Study Design: Observational / Descriptive / Cross sectional study.Place and Duration of Study: This study was conducted in medicine, surgery and allied departments of BVH, NHM, and JHL from April to June 2016.Materials and Methods: A total of 210 participants took part in the study; there were 70 participants from each of the three hospitals. The sample was taken by Stratified proportionate sampling technique. The Post-Graduate Residents were given performed questionnaires to fill out. The data was analyzed by SPSS 13 and all results were presented in the form of frequencies, percentages, and tables.Results: All of the Post-Graduate Residents who were handed out the questionnaires responded, and therefore, the response rate was 100%. 77.2% of the Post-Graduate Residents were found to be neutral, while 22.8% were satisfied.Conclusions: Most of the Post-Graduate Residents were found to have a neutral response towards their professional satisfaction. The Post-Graduate Residents in BVH were more inclined towards a response of being professionally satisfied. The most popularly agreed upon workplace related factor was good working relations with colleagues.